Comparative analysis of antibiotic prophylaxis guidelines in cardiac surgery: a survey in Czechia and Slovakia - Kubíčková, V; Poruba, M; Halačová, M (The Journal of hospital infection, 2025)
BACKGROUND: Surgical site infections (SSIs) in cardiac surgery significantly impact patient outcomes. This study examines cardiac antimicrobial prophylaxis guidelines in Czech and Slovak hospitals, crucial for reducing SSI incidence. METHODS: An electronic survey was conducted across cardiac surgery departments in both countries, focusing on surgical antibiotic prophylaxis (SAP) protocols, antibiotic choices, dosages, timing and postoperative infection rates. Responses were collected over three months, ensuring a comprehensive overview. FINDINGS: Most surveyed hospitals (79%) implement SAP, but guidelines exhibit notable variability. Cefazolin dominates as the primary prophylactic choice, with varying dosing regimens. Challenges include timing inconsistencies and prolonged prophylaxis durations, particularly in implant-related procedures. Regular guideline revisions are reported in 18% of hospitals within the last year, emphasizing the need for updated practices. CONCLUSIONS: This study shows the importance of standardizing SAP practices, aligning them with evolving evidence, and implementing regular guideline revisions. The observed variations highlight opportunities for enhanced SSI prevention strategies in cardiac surgery, ultimately contributing to improved patient outcomes.
Keywords: kardiochirurgické výkony; infekce chirurgické rány; Surveys and Questionnaires; Humans; Antibiotic Prophylaxis; Cardiac surgery; lidé; antibakteriální látky; Slovakia; Slovenská republika; Surgical Wound Infection; Antibiotic prophylaxis; průzkumy a dotazníky; Cardiac Surgical Procedures; antibiotická profylaxe; Practice Guidelines as Topic; Hospitals; Anti-Bacterial Agents; Surgical site infection; Czech Republic; nemocnice; směrnice pro lékařskou praxi jako téma; Česká republika